"Battling something bigger than me": A phenomenological investigation of generational trauma in African American women. (28th September 2022) - Petion, Ashlei R.; Chang, Catherine Y.; Brown‐Thompson, Crystal; Mitchell, Michelle D.; Grinnage, Deaetta; Huffstead, Mary E.
Abstract: The lived experiences of eight African American women college students were explored from an interpretive phenomenological analytic framework. The researchers identified six main themes about participants and their reported family dynamics: (a) collectivistic yet disconnected, (b) avoidance, (c) functioning in dysfunction, (d) gendered differences, (e) motivation to change the family's homeostasis, and (f) talking about generational trauma as a motivator to repair communication. Implications for culturally responsive counseling and generational trauma‐informed counselor training are discussed.